Liquid crystal alignment agent, liquid crystal alignment film, liquid crystal display element and diamine
By using a polymer obtained by a specific structure of diamine in the liquid crystal alignment agent, the problem of highlights of the liquid crystal display element under pressure and scratch conditions is solved, and the adhesion and strength of the liquid crystal alignment film is improved, thus achieving more High reliability and closeness.
Patent Information
- Application Number
- CN202080026107.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-11
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-03-11
AI Technical Summary
When the existing liquid crystal display element is under pressure, the liquid crystal alignment film cannot effectively limit the orientation of the liquid crystal, resulting in bright spots, and the adhesion between the polyimide-based liquid crystal alignment film and the sealant and substrate is insufficient.
By introducing a polymer obtained by diamine of a specific structure into the liquid crystal aligning agent, the characteristics of the liquid crystal aligning film are improved, and its orientation control to the liquid crystal and its adhesion to the sealant and substrate are enhanced.
It realizes that under physical friction conditions such as pressure and scratches, the emergence of highlights is reduced, the reliability and adhesion of the liquid crystal display element is improved, and the strength of the liquid crystal orientation film is enhanced.
Smart Images

Figure CN113711117B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polymer for a liquid crystal display element, a liquid crystal alignment agent, a liquid crystal alignment film and a liquid crystal display element, and a novel diamine for use therein. Background Art
[0002] In liquid crystal display elements, various driving methods have been developed that differ in electrode structure, physical properties of liquid crystal molecules used, manufacturing processes, etc., such as the known: TN (twisted nematic) type, STN (super-twisted nematic) type, VA (vertical alignment) type, MVA (multi-domain vertical alignment) type, IPS (in-plane switching) type, FFS (fringe field switching) type, PSA (polymer-sustained alignment) type and other liquid crystal display elements.
[0003] These liquid crystal display elements have a liquid crystal alignment film for aligning liquid crystal molecules. The material of the liquid crystal alignment film is generally a film formed of a polymer such as polyamic acid, polyimide, or polysiloxane, because of its excellent properties such as heat resistance, mechanical strength, and affinity with liquid crystal.
[0004] In recent years, the demand for high-quality images of liquid crystal display elements has become increasingly high. In particular, in displays of medical equipment and liquid crystal televisions, residual images, so-called "afterimages", have become a major problem when they are driven for a long time, and there is a high demand for reducing afterimages. From the perspective of further improving the quality of liquid crystal display elements, it is ideal to obtain liquid crystal display elements that are less likely to produce afterimages than before.
[0005] In view of such a situation, a liquid crystal alignment film and a liquid crystal alignment agent that provide a liquid crystal display element excellent in reducing the afterimage are known (for example, refer to Patent Document 1, Patent Document 2, and Patent Document 3).
[0006] In addition, the liquid crystal display elements used in the above-mentioned applications are also required to have the ability to withstand long-term use in harsh usage environments. Patent document 4 discloses that a liquid crystal alignment agent containing specific compounds can produce a liquid crystal alignment film with little reduction in voltage retention even after long-term exposure to backlight, thereby obtaining a liquid crystal display element with high reliability.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2016 / 063834 Pamphlet
[0010] Patent Document 2: International Publication No. 2015 / 060366 Pamphlet
[0011] Patent Document 3: Japanese Patent Application Publication No. 2018-054761
[0012] Patent Document 4: International Publication No. 2010 / 074269 Pamphlet Summary of the invention
[0013] Problems to be solved by the invention
[0014] In addition, so-called touch panel type liquid crystal display elements are widely used, and users frequently apply strong pressure to the display element with their fingers. At this time, the spacer inside the liquid crystal display element moves inside the liquid crystal display element and scratches the liquid crystal alignment film. This becomes the following technical problem: the liquid crystal alignment film, which is pressured by the spacer, cannot restrict the orientation of the liquid crystal, and even if the liquid crystal display element is displayed black, for example, light leaks from the periphery of the spacer and is displayed as a bright spot.
[0015] The composition of the liquid crystal alignment agent proposed in the past cannot necessarily solve all the above problems. The present invention is completed based on the above situation, and its purpose is to provide a liquid crystal display element with less afterimages and minimize bright spots even when physical friction such as scratches caused by spacers occurs, and with high reliability. In addition, a liquid crystal alignment film and a liquid crystal alignment agent with high film strength suitable for such a liquid crystal display element are provided.
[0016] In addition, in order to enlarge the effective pixel area in the recent liquid crystal display element, it is required that no pixels are formed on the peripheral outer edge of the substrate, so that the so-called frame area is smaller and smaller. With the narrow frame of the panel, the sealant used when bonding two substrates to make a liquid crystal display element is applied to the polyimide liquid crystal alignment film, but there is the following problem: there is no polar group on the polyimide, so it is impossible to form a covalent bond with the sealant on the surface of the liquid crystal alignment film, and the bonding between the substrates is insufficient. Therefore, it becomes a problem to improve the adhesion (closeness) of the polyimide liquid crystal alignment film to the sealant and the substrate.
[0017] Solutions for solving problems
[0018] The present inventors have conducted intensive studies to solve the above problems and have found that various properties can be improved simultaneously by introducing a specific structure into a polymer contained in a liquid crystal aligning agent, thereby completing the present invention. The present invention is based on the above findings and has the following contents as the main points.
[0019] 1. A liquid crystal aligning agent comprising a polymer obtained from a diamine having a structure represented by the following formula (1).
[0020]
[0021] In formula (1), A represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a benzyl group, a p-methoxybenzyl group, an alkoxy group having 1 to 3 carbon atoms, an acetyl group, a benzoyl group, a tert-butoxycarbonyl group, a 9-fluorenylmethoxycarbonyl group or a R1R2R3Si group, and R1, R2 and R3 each independently represent an alkyl group having 1 to 3 carbon atoms or a phenyl group.
[0022] Effects of the Invention
[0023] According to the liquid crystal aligning agent of the present invention, generation of afterimages is small and even when physical friction such as scratches by spacers occurs, a liquid crystal display element capable of minimizing bright spots and a liquid crystal aligning film providing the above effects can be obtained.
[0024] According to the liquid crystal alignment agent of the present invention, a liquid crystal alignment film with excellent adhesion to the sealant can be obtained. By using the liquid crystal alignment film, a liquid crystal display element with excellent adhesion to each other and strong impact resistance can be obtained. The mechanism for improving the adhesion to the sealant is not necessarily clear, but it is considered as follows: the hydroxyl group, methoxy group or hydroxyl group generated by heating and removing the protective group possessed by the specific diamine is exposed on the surface of the liquid crystal alignment film, and the interaction between the functional group in the group and the sealant improves the adhesion of the liquid crystal alignment film to the sealant. DETAILED DESCRIPTION
[0025] The liquid crystal aligning agent of the present invention is a liquid crystal aligning agent containing a polymer (hereinafter also referred to as a specific polymer) obtained from a diamine having a structure represented by the above formula (1). Hereinafter, each condition will be described in detail.
[0026] <Diamines having specific structures>
[0027] The polymer of the present invention is a polymer obtained from a diamine having a structure of the above formula (1).
[0028] Specific examples of the diamine of the formula (1) are as follows, but are not limited thereto. Among them, (1-1), (1-2), and (1-3) are particularly preferred from the viewpoint of alleviating the accumulated charge.
[0029]
[0030] <Polymer>
[0031] The polymer of the present invention is a polymer obtained by using the above-mentioned diamine. As specific examples, polyamic acid, polyamic acid ester, polyimide, polyurea, polyamide, etc. can be listed, but from the viewpoint of being used as a liquid crystal aligning agent, it is more preferably selected from at least one of a polyimide precursor containing a structural unit represented by the following formula (6) and a polyimide as an imide product of the polyimide precursor.
[0032]
[0033] In the above formula (6), X1 is a tetravalent organic group derived from a tetracarboxylic acid derivative, Y1 is a divalent organic group derived from a diamine having a structure of formula (1), and R4 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms. In view of the ease of imidization by heating, R4 is preferably a hydrogen atom, a methyl group or an ethyl group.
[0034] <<Tetracarboxylic dianhydride>>
[0035] X1 is a tetravalent organic group derived from a tetracarboxylic acid derivative, and its structure is not particularly limited. In addition, X1 in the polyimide precursor can be appropriately selected according to the degree of characteristics required for the solubility of the polymer in the solvent, the coating property of the liquid crystal aligning agent, the orientation of the liquid crystal when the liquid crystal aligning film is made, the voltage holding rate, the accumulated charge, etc., and can be one in the same polymer, or two or more can be mixed.
[0036] Specific examples of X1 include structures of formulae (X-1) to (X-46) described in claims 13 to 14 of International Publication No. 2015 / 119168.
[0037] Preferred structures of X1 are shown below, but the present invention is not limited thereto.
[0038]
[0039] Among the above structures, (A-1) and (A-2) are particularly preferred from the viewpoint of photo-orientation, (A-4) is particularly preferred from the viewpoint of further improving the relaxation rate of accumulated charge, and (A-15) to (A-17) are particularly preferred from the viewpoint of liquid crystal orientation and further improving the relaxation rate of accumulated charge.
[0040] <<Polymer (other structural units)>>
[0041] The polyimide precursor containing the structural unit represented by formula (6) may contain at least one selected from the structural unit represented by formula (7) below and polyimides which are imide products thereof, within a range not impairing the effects of the present invention.
[0042]
[0043] In formula (7), X2 is a tetravalent organic group derived from a tetracarboxylic acid derivative, Y2 is a divalent organic group derived from a diamine that does not contain the structure of formula (1) in the main chain direction, R5 has the same definition as R4 in formula (6), and R6 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. In addition, at least one of the two R6s is preferably a hydrogen atom.
[0044] As a specific example of X2, it is possible to list: a structure identical to the structure shown by the example of X1 in formula (6) which also includes preferred examples. In addition, Y2 in the polyimide precursor is a divalent organic group derived from a diamine having a structure not including formula (1) in the main chain direction, and its structure is not particularly limited. In addition, Y2 can be appropriately selected according to the degree of characteristics required for the solubility of the polymer in the solvent, the coating property of the liquid crystal aligning agent, the orientation of the liquid crystal in the case of making a liquid crystal aligning film, the voltage retention rate, the accumulated charge, etc., and can be one in the same polymer, or two or more can be mixed.
[0045] Specific examples of Y2 include: the structure of formula (2) described in claim 4 of International Publication No. 2015 / 119168, and the structures of formulas (Y-1) to (Y-97) and (Y-101) to (Y-118) described in claims 8 to 12; a divalent organic group obtained by removing two amino groups from formula (2) described in claim 6 of International Publication No. 2013 / 008906; and a divalent organic group obtained by removing two amino groups from formula (2) described in claim 7 of International Publication No. 2015 / 122413. The divalent organic group obtained by removing two amino groups from the formula (1) described in claim 8 of ; the structure of the formula (3) described in claim 8 of International Publication No. 2015 / 060360; the divalent organic group obtained by removing two amino groups from the formula (1) described in claim 8 of Japanese Patent Publication No. 2012-173514; the divalent organic group obtained by removing two amino groups from the formulas (A) to (F) described in claim 9 of International Publication No. 2010-050523, etc.
[0046] Preferred structures of Y2 are shown below, but the present invention is not limited thereto.
[0047]
[0048]
[0049] Among the above structures, from the perspective of further improving film strength, (B-28), (B-29) and the like are particularly preferred, from the perspective of further improving liquid crystal orientation, (B-1) to (B-3) and the like are particularly preferred, from the perspective of further improving the relaxation rate of accumulated charge, (B-14) to (B-18) and (B-27) and the like are particularly preferred, and from the perspective of further improving voltage holding rate, the like, (B-26) and the like are preferred.
[0050] When the polyimide precursor containing the structural unit represented by formula (6) also contains the structural unit represented by formula (7), the structural unit represented by formula (6) is preferably 10 mol% or more, more preferably 15 mol% or more, and particularly preferably 20 mol% or more, relative to the total of formula (6) and formula (7).
[0051] The molecular weight of the polyimide precursor used in the present invention is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and further preferably 10,000 to 100,000 in terms of weight average molecular weight.
[0052] Examples of polyimides having a divalent group represented by formula (1) in the main chain include polyimides obtained by ring-closing the above-mentioned polyimide precursor. In the polyimide, the ring-closing ratio (also called imidization ratio) of the amic acid group does not necessarily need to be 100% and can be arbitrarily adjusted according to the application and purpose.
[0053] As a method for imidating a polyimide precursor, thermal imidation in which a solution of a polyimide precursor is directly heated, or catalytic imidation in which a catalyst is added to a solution of a polyimide precursor can be exemplified.
[0054] The liquid crystal aligning agent of the present invention is a composition containing the above-mentioned specific polymer and an organic solvent, and may also contain two or more specific polymers of different structures. In addition, the liquid crystal aligning agent of the present invention may also contain polymers other than the specific polymer (hereinafter, also referred to as the second polymer) and various additives as long as the effect described in the present invention is exerted within the limits.
[0055] When the liquid crystal aligning agent of the present invention contains a second polymer, it is preferable that the ratio of the specific polymer to all polymer components is 5 mass % or more, and 5 to 95 mass % is mentioned as an example thereof.
[0056] Examples of the second polymer include polyamic acid, polyimide, polyamic acid ester, polyester, polyamide, polyurea, polyorganosiloxane, cellulose derivatives, polyacetal, polystyrene or derivatives thereof, poly(styrene-phenylmaleimide) derivatives, and poly(meth)acrylate.
[0057] In particular, a polyamic acid obtained from a tetracarboxylic dianhydride component and a diamine component (hereinafter, also referred to as a second polyamic acid) is preferred as the second polymer.
[0058] Examples of the tetracarboxylic dianhydride component for obtaining the second polyamic acid include compounds represented by the following formula (11): The acid dianhydride component may be composed of one compound or may be composed of two or more compounds.
[0059]
[0060] In formula (11), A is a tetravalent organic group, preferably a tetravalent organic group having 4 to 30 carbon atoms.
[0061] Specific examples of A include the same structures as those exemplified in X1 in formula (6), including preferred examples.
[0062] As a diamine component for obtaining the 2nd polyamic acid, it can determine suitably according to the objective, For example, the diamine represented by following formula (12) can be used.
[0063]
[0064] (Y9 represents a divalent organic group. A9 are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an alkynyl group having 2 to 5 carbon atoms, and may be the same or different. From the viewpoint of liquid crystal orientation, A9 is preferably a hydrogen atom or a methyl group.)
[0065] Hereinafter, the structure of Y9 of the formula (12) preferably used as the diamine component for obtaining the second polyamic acid is shown, but the present invention is not limited thereto.
[0066]
[0067] For the purpose of improving electrical properties and relaxing properties, Y9 is preferably a divalent organic group having a secondary or tertiary nitrogen atom, or a divalent organic group having -NH-CO-NH- in the molecule. When Y9 is a divalent organic group having a secondary or tertiary nitrogen atom, specific examples of formula (12) include: a diamine having a pyrrole structure as described in International Publication WO2017 / 126627, preferably a diamine having a structure as shown in the following formula (pr); a diamine having a pyrrole structure as described in International Publication WO2018 / 062197, preferably a diamine having a structure as shown in the following formula (pn); a diamine having a carbazole structure as described in International Publication WO2018 / 110354, preferably a diamine having a structure as shown in the following formula (pn); A diamine having a structure represented by formula (cz); a diamine having a nitrogen-containing heterocyclic ring as described in paragraphs
[0173] to
[0188] of International Publication WO2015 / 046374, a diamine having a nitrogen-containing structure as described in paragraph
[0050] of Japanese Patent Application Laid-Open No. 2016-218149, a diamine represented by the following formula (BP); 2,3-diaminopyridine, 2,6-diaminopyridine, 3,4-diaminopyridine, 2,4-diaminopyrimidine, 5,6-diamino-2,3-dicyanopyrazine, 5,6-diamino-2,4-dihydroxypyrimidine , 2,4-diamino-6-dimethylamino-1,3,5-triazine, 1,4-bis(3-aminopropyl)piperazine, 4,4'-[4,4'-propane-1,3-diylbis(piperidin-1,4-diyl)]diphenylamine, 2,4-diamino-6-isopropoxy-1,3,5-triazine, 2,4-diamino-6-methoxy-1,3,5-triazine, 2,4-diamino-6-phenyl-1,3,5-triazine, 2,4-diamino-6-methyl-1,3,5-triazine, 2,4-diamino-1,3,5-triazine, 4,6-diamino Amino-2-vinyl-1,3,5-triazine, 3,5-diamino-1,2,4-triazole, 6,9-diamino-2-ethoxyacridine lactate, 3,8-diamino-6-phenylphenanthridine, 1,4-diaminopiperazine, 3,6-diaminoacridine, bis(4-aminophenyl)-N-aniline, 4,4'-diaminodiphenyl-N-methylamine, 4,4'-diaminodiphenylamine, 3,6-diaminocarbazole, 9-methyl-3,6-diaminocarbazole, 9-ethyl-3,6-diaminocarbazole, diamines represented by the following formulas (w1) to (w2), and the like.
[0068]
[0069] (R 1 represents a hydrogen atom, a fluorine atom, a cyano group, a hydroxyl group, or a methyl group, and R 2 Each independently represents a single bond or a group "*1-R 3 -Ph-*2”,R 3represents a single bond, -O-, -COO-, -OCO-, -(CH2) l -, -O(CH2) m The divalent organic group in O-, -CONH- and -NHCO- (l and m represent integers of 1 to 5, *1 represents the site bonded to the benzene ring in the formula (pr), and *2 represents the site bonded to the amino group in the formula (pr). Ph represents a phenylene group. n represents 1 to 3.)
[0070]
[0071] (R 1 and R 2 Each independently represents a hydrogen atom or a methyl group, R 3 Indicates a single bond or group "*1-R 4 -Ph-*2”,R 4 represents a single bond, -O-, -COO-, -OCO-, -(CH2) l -, -O(CH2) m The divalent organic group in O-, -CONH- and -NHCO- (l and m represent integers of 1 to 5, *1 represents the site bonded to the benzene ring in the formula (pn), and *2 represents the site bonded to the amino group in the formula (pn). Ph represents a phenylene group. n represents 1 to 3.)
[0072]
[0073] (R 1 represents a hydrogen atom or a methyl group, R 2 represents a methyl group.)
[0074]
[0075] (X is a biphenyl skeleton or a fluorene ring, Y is a group selected from a benzene ring, a biphenyl skeleton or -Ph-Z-Ph- (Ph represents a phenylene group), and Z is a divalent group represented by -O-, -NH-, -CH2-, -SO2-, -C(CH3)2- or -C(CF3)2-. A and B are hydrogen atoms or methyl groups.)
[0076]
[0077] (Sp represents phenylene, pyrrolidine, piperidine, piperazine, a divalent chain hydrocarbon group having 2 to 20 carbon atoms, or a group in which -CH2- of the divalent chain hydrocarbon group is substituted with a group selected from -O-, -CO-, -CO-O-, -NRCO- (R represents a hydrogen atom or a methyl group), -NRCOO- (R represents a hydrogen atom or a methyl group), -CONR- (R represents a hydrogen atom or a methyl group), -COS-, -NR- (R represents a methyl group), pyrrolidine, piperidine, and piperazine.)
[0078] When Y9 is a divalent organic group having -NH-CO-NH- in the molecule, as specific examples of the above formula (12), diamines in the following cases can be listed: in the following formula (4), A1 is -NH-CO-NH-, or a group in which at least one of the -CH2- in an alkylene group having 2 to 20 carbon atoms is substituted with -NH-CO-NH-, or a group in which at least one of the -CH2- in an alkylene group having 2 to 20 carbon atoms is substituted with -NH-CO-NH-, and at least one of the other -CH2- is substituted with a group selected from -O-, -CO-, -CO-O-, -NRCO- (R represents a hydrogen atom or a methyl group), -NRCOO- (R represents a hydrogen atom or a methyl group), -CONR- (R represents a hydrogen atom or a methyl group), -COS-, and -NR- (R represents a methyl group) substituted. Specific examples of more preferred diamines include diamines represented by the following formulas (U-1) to (U-9), etc.
[0079]
[0080] (A1 represents a single bond, -NH-CO-NH-, or an alkylene group having 2 to 20 carbon atoms (wherein any -CH2- of the alkylene group may be substituted with -O-, -CO-, -CO-O-, -NRCO- (R represents a hydrogen atom or a methyl group), -NRCOO- (R represents a hydrogen atom or a methyl group), -CONR- (R represents a hydrogen atom or a methyl group), -COS-, -NR- (R represents a methyl group), or -NH-CO-NH-). A2 represents a halogen atom, a hydroxyl group, or an alkyl or alkoxy group having 1 to 5 carbon atoms (wherein any hydrogen atom of the alkyl or alkoxy group may be substituted with a halogen atom). a is an integer of 0 to 4, and when a is 2 or more, A2 may be the same or different. b and c are each independently an integer of 1 to 2.)
[0081]
[0082] Preferred specific examples of the diamines represented by the above formulae (w1) to (w2) include diamines represented by the following formulae (n3-1) to (n3-7) and diamines represented by the following formulae (n4-1) to (n4-6).
[0083]
[0084] For the purpose of improving printability, diamine compounds having a carboxyl group (COOH group) or a hydroxyl group (OH group) may also be used. Specifically, 2,4-diaminophenol, 3,5-diaminophenol, 3,5-diaminobenzyl alcohol, 2,4-diaminobenzyl alcohol, 4,6-diaminoresorcinol, 2,4-diaminobenzoic acid, 2,5-diaminobenzoic acid or 3,5-diaminobenzoic acid may be mentioned. Among them, 2,4-diaminobenzoic acid, 2,5-diaminobenzoic acid or 3,5-diaminobenzoic acid is preferred. In addition, diamine compounds represented by the following formulas [3b-1] to [3b-4] and diamine compounds whose amino groups are secondary amino groups may be used.
[0085]
[0086] (In formula [3b-1], Q 1 represents a single bond, -CH2-, -C2H4-, -C(CH3)2-, -CF2-, -C(CF3)2-, -O-, -CO-, -NH-, -N(CH3)-, -CONH-, -NHCO-, -CH2O-, -OCH2-, -COO-, -OCO-, -CON(CH3)-, or -N(CH3)CO-, m 1 and m 2 Each independently represents an integer from 0 to 4, and m 1 +m 2 represents an integer of 1 to 4, and in formula [3b-2], m 3 and m 4 Each independently represents an integer of 1 to 5. In the formula [3b-3], Q 2 represents a straight or branched alkylene group having 1 to 5 carbon atoms, m 5 represents an integer of 1 to 5, in formula [3b-4], Q 3 and Q 4 Each independently represents a single bond, -CH2-, -C2H4-, -C(CH3)2-, -CF2-, -C(CF3)2-, -O-, -CO-, -NH-, -N(CH3)-, -CONH-, -NHCO-, -CH2O-, -OCH2-, -COO-, -OCO-, -CON(CH3)- or -N(CH3)CO-, m 6 Indicates an integer from 1 to 4. )
[0087] As the diamine component for obtaining the second polyamic acid, diamines used for specific polymers and known diamines can be used in addition to the above, but the present invention is not limited thereto. The diamine component for obtaining the second polyamic acid may be one diamine or two or more diamines may be used in combination.
[0088] <Production method of polyamic acid, polyamic acid ester, and polyimide>
[0089] The polyamic acid ester, the polyamic acid, and the polyimide which are polyimide precursors used in the present invention can be synthesized by a known method described in, for example, International Publication WO2013 / 157586.
[0090] <Liquid crystal alignment agent>
[0091] The liquid crystal aligning agent of the present invention contains a polymer (A). In addition to the polymer (A) and the desired second polymer, the liquid crystal aligning agent of the present invention may also contain other polymers. As the types of other polymers, polyamic acid, polyimide, polyamic acid ester, polyester, polyamide, polyurea, polyorganosiloxane, cellulose derivatives, polyacetals, polystyrene or its derivatives, poly(styrene-phenylmaleimide) derivatives, poly(meth)acrylates, etc. can be listed.
[0092] The liquid crystal alignment agent is used to make a liquid crystal alignment film. From the perspective of forming a uniform film, it is preferably in the form of a coating liquid. In the liquid crystal alignment agent of the present invention, a coating liquid containing the above-mentioned polymer component and an organic solvent is preferred. At this time, the concentration of the polymer in the liquid crystal alignment agent can be appropriately changed according to the setting of the thickness of the coating film to be formed. From the perspective of forming a uniform and defect-free coating film, it is preferably more than 1% by mass, and from the perspective of the storage stability of the solution, it is preferably less than 10% by mass. The concentration of the polymer is particularly preferably 2 to 8% by mass.
[0093] The organic solvent contained in the liquid crystal alignment agent is not particularly limited as long as it is a solvent in which the polymer component can be uniformly dissolved. If specific examples are listed, they include: N, N-dimethylformamide, N, N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, γ-butyrolactone, 1, 3-dimethyl-2-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 3-methoxy-N, N-dimethylpropionamide, 3-butoxy-N, N-dimethylpropionamide (they are also collectively referred to as "good solvents"), etc. Among them, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 3-methoxy-N, N-dimethylpropionamide, 3-butoxy-N, N-dimethylpropionamide or γ-butyrolactone is preferably used. The good solvent in the liquid crystal aligning agent of the present invention is preferably 20 to 99% by mass of the whole solvent contained in the liquid crystal aligning agent, more preferably 20 to 90% by mass, particularly preferably 30 to 80% by mass.
[0094] In addition, the organic solvent contained in the liquid crystal aligning agent is preferably a mixed solvent of a solvent (also called a poor solvent) that improves the coating property and surface smoothness of the coating film when the liquid crystal aligning agent is applied, in addition to the above-mentioned solvents. Specific examples of the organic solvents used in combination are listed below, but are not limited to these examples.
[0095] For example, diisopropyl ether, diisobutyl ether, diisobutyl carbinol (2,6-dimethyl-4-heptanol), ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 4-hydroxy-4-methyl-2-pentanone, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, ethylene glycol monoacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, ethylene glycol monobutyl ether, ethylene glycol monoisopentyl ether, ethylene glycol monohexyl ether, propylene glycol monobutyl ether, 1-(2-butoxyethoxy)-2-propanol, 2 -(2-Butoxyethoxy)-1-propanol, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, ethylene glycol monobutyl ether acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, propylene glycol diacetate, n-butyl acetate, propylene glycol monoethyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, propyl 3-methoxypropionate, butyl 3-methoxypropionate, n-butyl lactate, isopentyl lactate, diethylene glycol monoethyl ether, diisobutyl ketone (2,6-dimethyl-4-heptanone), etc.
[0096] Among them, diisobutylcarbinol, propylene glycol monobutyl ether, propylene glycol diacetate, diethylene glycol diethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol dimethyl ether, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monobutyl ether, ethylene glycol monobutyl ether acetate, and diisobutyl ketone are preferably used.
[0097] Preferred combinations of good solvents and poor solvents include: N-methyl-2-pyrrolidone and ethylene glycol monobutyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone and ethylene glycol monobutyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone and propylene glycol monobutyl ether; N-ethyl-2-pyrrolidone and propylene glycol monobutyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone, 4-hydroxy-4-methyl-2-pentanone and diethylene glycol diethyl ether; N-methyl -2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and 2,6-dimethyl-4-heptanone; N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and diisopropyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone, propylene glycol monobutyl ether and 2,6-dimethyl-4-heptanol; N-methyl-2-pyrrolidone, γ-butyrolactone and dipropylene glycol dimethyl ether; N-methyl-2-pyrrolidone, γ-butyrolactone and dipropylene glycol dimethyl ether, etc. These poor solvents are preferably 1 to 80% by mass of the total solvent contained in the liquid crystal alignment agent, more preferably 10 to 80% by mass, and particularly preferably 20 to 70% by mass. The type and content of such solvents are appropriately selected according to the coating device, coating conditions, coating environment, etc. of the liquid crystal alignment agent.
[0098] The liquid crystal aligning agent of the present invention may also contain additional components other than the polymer component and the organic solvent. Such additional components include: a bonding aid for improving the adhesion between the liquid crystal aligning film and the substrate, the adhesion between the liquid crystal aligning film and the sealant, a compound for improving the strength of the liquid crystal aligning film (hereinafter also referred to as a cross-linking compound), a dielectric for adjusting the dielectric constant and resistance of the liquid crystal aligning film, a conductive material, etc.
[0099] As the cross-linking compound, from the viewpoint of less generation of AC afterimages and high improvement effect of film strength, it is preferred to use a compound having at least one group selected from the group consisting of an oxiranyl group, an oxetane group, a protected isocyanate group, a protected isothiocyanate group, a group containing an oxazoline ring structure, a group containing a Meldrum acid structure, a cyclocarbonate group and a group represented by the following formula (d), or a compound selected from the compounds represented by the following formula (e) (hereinafter, they are also collectively referred to as compound (C)).
[0100]
[0101] (Where R 71 is a hydrogen atom, an alkyl group with 1 to 3 carbon atoms, or "*-CH2-OH", R 72 and R 73Each of them is independently a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or "*-CH2-OH". * represents a bond. A represents an (m+n)-valent organic group having an aromatic ring. m represents an integer of 1 to 6, and n represents an integer of 0 to 4.)
[0102] Specific examples of compounds having an oxirane group include, for example, compounds described in paragraph
[0037] of Japanese Patent Publication No. 10-338880, compounds having a triazine ring in the skeleton described in International Publication No. WO2017 / 170483, and compounds having two or more oxirane groups. Among them, compounds containing nitrogen atoms such as N,N,N',N',-tetraglycidyl-m-xylene diamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N',-tetraglycidyl-4,4'-diaminodiphenylmethane, N,N,N',N'-tetraglycidyl-p-phenylenediamine, and compounds represented by the following formulas (r-1) to (r-3) are particularly preferred.
[0103]
[0104] Specific examples of the compound having an oxetane group include compounds having two or more oxetane groups described in paragraphs
[0170] to
[0175] of International Publication No. 2011 / 132751.
[0105] Specific examples of compounds having protected isocyanate groups include compounds having two or more protected isocyanate groups described in paragraphs
[0046] to
[0047] of Japanese Patent Application Laid-Open No. 2014-224978, compounds having three or more protected isocyanate groups described in paragraphs
[0119] to
[0120] of International Publication No. 2015 / 141598, etc. Among them, compounds represented by the following formulas (bi-1) to (bi-3) are preferred.
[0106]
[0107] Specific examples of the compound having a protected isothiocyanate group include compounds having two or more protected isothiocyanate groups described in JP-A-2016-200798.
[0108] Specific examples of the compound having a group containing an oxazoline ring structure include compounds containing two or more oxazoline structures described in paragraph
[0115] of JP-A-2007-286597.
[0109] Specific examples of the compound having a group containing a Michaelis acid structure include compounds having two or more Michaelis acid structures described in International Publication No. WO2012 / 091088.
[0110] Specific examples of the compound having a cyclic carbonate group include compounds described in International Publication No. WO2011 / 155577.
[0111] As R in the above formula (d) 71 , R 72 , R 73 The alkyl group having 1 to 3 carbon atoms includes, for example, a methyl group, an ethyl group, and a propyl group.
[0112] Specific examples of the compound having a group represented by the above formula (d) include, for example, the compound having two or more groups represented by the above formula (d) described in paragraph
[0058] of International Publication WO2015 / 072554 and Japanese Patent Application Publication No. 2016-118753, and the compound described in Japanese Patent Application Publication No. 2016-200798. Among them, the compounds represented by the following formulas (hd-1) to (hd-8) are preferred.
[0113]
[0114] Examples of the (m+n)-valent organic group having an aromatic ring in A of the above formula (e) include: an (m+n)-valent aromatic hydrocarbon group having 5 to 30 carbon atoms, an (m+n)-valent organic group to which an aromatic hydrocarbon group having 5 to 30 carbon atoms is directly or via a linking group, and an (m+n)-valent group having an aromatic heterocyclic ring. Examples of the aromatic hydrocarbon group include benzene and naphthalene. Examples of the aromatic heterocyclic ring include: a pyrrole ring, an imidazole ring, a pyrazole ring, a pyridine ring, a pyrimidine ring, a quinoline ring, an isoquinoline ring, a carbazole ring, a pyridazine ring, a pyrazine ring, a benzimidazole ring, a benzimidazole ring, an indole ring, a quinoxaline ring, an acridine ring, and the like. Examples of the linking group include: an alkylene group having 1 to 10 carbon atoms, a group obtained by removing one hydrogen atom from the alkylene group, a divalent or trivalent cyclohexane ring, and the like. It should be noted that any hydrogen atom of the alkylene group may be substituted with a fluorine atom or an organic group such as a trifluoromethyl group. Specific examples include compounds described in International Publication No. WO2010 / 074269. Preferred specific examples include the following formulas (e-1) to (e-9).
[0115]
[0116] The above compound is an example of a crosslinking compound, but is not limited thereto. For example, components other than the above disclosed on pages 53 to 55 of International Publication No. 2015 / 060357 can be cited. In addition, the crosslinking compound contained in the liquid crystal aligning agent of the present invention may be one kind or a combination of two or more kinds.
[0117] The content of the crosslinking compound in the liquid crystal aligning agent of the present invention is preferably 0.5 to 20 parts by mass relative to 100 parts by mass of the polymer component contained in the liquid crystal aligning agent, and is more preferably 1 to 15 parts by mass from the viewpoint of allowing the crosslinking reaction to proceed, achieving the target effect, and reducing the generation of AC afterimages.
[0118] Examples of the adhesion aid include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldiethoxymethylsilane, 2-aminopropyltrimethoxysilane, 2-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane. Ethoxycarbonyl-3-aminopropyl triethoxysilane, N-triethoxysilylpropyl triethylenetriamine, N-trimethoxysilylpropyl triethylenetriamine, 10-trimethoxysilyl-1,4,7-triazadecane, 10-triethoxysilyl-1,4,7-triazadecane, 9-trimethoxysilyl-3,6-diazanonyl acetate, 9-triethoxysilyl-3,6-diazanonyl acetate, N-benzyl-3-aminopropyl trimethoxysilane, N-benzyl-3-aminopropyl triethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, N-bis(oxyethylene)-3-aminopropyltrimethoxysilane, N-bis(oxyethylene)-3-aminopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-epoxy Silane coupling agents such as propoxypropyl triethoxysilane, p-styryl trimethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl methyl diethoxysilane, 3-methacryloxypropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane, tris (trimethoxysilylpropyl) isocyanurate, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl trimethoxysilane, and 3-isocyanate propyl triethoxysilane. When using these silane coupling agents, from the viewpoint of less generation of AC residual images, the amount is preferably 0.1 to 30 parts by mass, and more preferably 0.1 to 20 parts by mass, relative to 100 parts by mass of the polymer component contained in the liquid crystal aligning agent.
[0119] <Liquid crystal alignment film / liquid crystal display element>
[0120] A liquid crystal alignment film can be manufactured by using the above-mentioned liquid crystal alignment agent. In addition, the liquid crystal display element of the present invention has a liquid crystal alignment film formed by using the above-mentioned liquid crystal alignment agent. The operation mode of the liquid crystal display element of the present invention is not particularly limited, for example, it can be applied to various operation modes such as TN (Twisted Nematic) type, STN type, vertical alignment type (including VA-MVA type, VA-PVA type, etc.), in-plane switching type (IPS type), FFS (Fringe Field Switching) type, optically compensated bending type (OCB type: Optically Compensated Birefringence type).
[0121] The liquid crystal display element of the present invention can be produced, for example, by a process including the following steps (1-1) to (1-3). In step (1-1), different substrates are used depending on the desired operation mode. Steps (1-2) and (1-3) are common to each operation mode.
[0122] [Step (1-1): Formation of coating film]
[0123] First, the liquid crystal aligning agent of the present invention is applied on a substrate, and then the applied surface is heated to form a coating film on the substrate.
[0124] (1-1A)
[0125] For example, in the case of manufacturing a TN type, STN type or VA type liquid crystal display element, first, two substrates provided with patterned transparent conductive films are used as a pair, and the liquid crystal alignment agent prepared in the above is applied to each transparent conductive film forming surface thereof by preferably offset printing, spin coating, roll coating or inkjet printing. As a substrate, for example, a transparent substrate composed of glass such as float glass and soda glass; plastics such as polyethylene terephthalate, polybutylene terephthalate, polyether sulfone, polycarbonate, and poly (alicyclic olefin) can be used. As a transparent conductive film provided on one side of the substrate, a NESA film (registered trademark of PPG Company, USA) composed of tin oxide (SnO2), an ITO film composed of indium oxide-tin oxide (In2O3-SnO2), etc. can be used. In order to obtain a patterned transparent conductive film, for example, the following methods may be used: a method of forming a transparent conductive film without a pattern and then forming a pattern by photolithography; a method of using a mask having a desired pattern when forming the transparent conductive film; etc. When applying the liquid crystal alignment agent, in order to further improve the adhesion between the substrate surface and the transparent conductive film and the coating film, a pretreatment may be performed by pre-coating a functional silane compound, a functional titanium compound, etc. on the surface of the substrate where the coating film is to be formed.
[0126] After the liquid crystal alignment agent is applied, it is preferred to perform preliminary heating (pre-baking) for the purpose of preventing the liquid of the applied liquid crystal alignment agent from dripping. The pre-baking temperature is preferably 30 to 200°C, more preferably 40 to 150°C, and particularly preferably 40 to 100°C. The pre-baking time is preferably 0.25 to 10 minutes, and more preferably 0.5 to 5 minutes. Afterwards, the solvent is completely removed, and as needed, a calcination (post-baking) process is performed for the purpose of thermally imidizing the amide acid structure present in the polymer. The calcination temperature (post-baking temperature) at this time is preferably 80 to 300°C, and more preferably 120 to 250°C. The post-baking time is preferably 5 to 200 minutes, and more preferably 10 to 100 minutes. The film thickness of the film formed in this way is preferably 0.001 to 1 μm, and more preferably 0.005 to 0.5 μm.
[0127] (1-1B)
[0128] In the case of manufacturing an IPS type or FFS type liquid crystal display element, a liquid crystal alignment agent is applied to the electrode forming surface of a substrate provided with an electrode composed of a transparent conductive film or metal film patterned into a comb shape and a side of an opposing substrate without an electrode, and then each coated surface is heated to form a coating film. The material of the substrate and transparent conductive film used at this time, the coating method, the heating conditions after coating, the patterning method of the transparent conductive film or metal film, the pretreatment of the substrate, and the preferred film thickness of the formed coating film are the same as those described above (1-1A). As a metal film, for example, a film composed of a metal such as chromium can be used.
[0129] In any of the above (1-1A) and (1-1B), a liquid crystal alignment film or a coating film of a liquid crystal alignment film is formed by applying a liquid crystal alignment agent to a substrate and then removing an organic solvent. In this case, the coating film may be further heated after formation to allow a dehydration ring-closure reaction of the polyamic acid, polyamic acid ester and polyimide used in the liquid crystal alignment agent of the present invention to proceed, thereby forming a coating film that has been further imidized.
[0130] [Step (1-2): Orientation-imparting treatment]
[0131] In the case of manufacturing TN type, STN type, IPS type or FFS type liquid crystal display elements, the coating formed in the above step (1-1) is subjected to a treatment of imparting liquid crystal orientation ability. As a result, the coating is endowed with the orientation ability of the liquid crystal molecules, and becomes a liquid crystal orientation film. As an orientation ability imparting treatment, for example, there can be listed: a brushing treatment in which a roll made of a cloth composed of fibers such as nylon, rayon, and cotton is wound to rub the coating in a certain direction; a light orientation treatment in which the coating is irradiated with polarized or non-polarized radiation, etc. On the other hand, in the case of manufacturing a VA type liquid crystal display element, the coating formed in the above step (1-1) can be directly used as a liquid crystal orientation film, or the coating can be subjected to an orientation ability imparting treatment.
[0132] In the case where the coating film is given liquid crystal orientation ability by photo-orientation treatment, as the radiation irradiated to the coating film, for example, ultraviolet rays and visible light containing wavelengths of 150 to 800 nm can be used. In the case where the radiation is polarized, it can be linearly polarized or partially polarized. In addition, in the case where the radiation used is linearly polarized or partially polarized, the irradiation can be performed from a direction perpendicular to the substrate surface, from an oblique direction, or in combination thereof. In the case of irradiating non-polarized radiation, the irradiation direction is set to an oblique direction.
[0133] As the light source used, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. Ultraviolet rays in a preferred wavelength range can be obtained by combining a light source with, for example, a filter, a diffraction grating, etc. The irradiation amount of the radiation is preferably 10 to 5000 mJ / cm 2 , more preferably 30 to 2000 mJ / cm 2 .
[0134] In order to improve the reactivity, the coating film may be irradiated with light while being heated. The temperature during heating is usually 30 to 250°C, preferably 40 to 200°C, and more preferably 50 to 150°C.
[0135] In addition, when ultraviolet rays containing light with a wavelength of 150 to 800 nm are used, the light irradiation film obtained in the above process can be used directly as a liquid crystal alignment film, or the light irradiation film can be calcined, cleaned with water or an organic solvent, or a combination thereof. The calcination temperature at this time is preferably 80 to 300 ° C, more preferably 80 to 250 ° C. The calcination time is preferably 5 to 200 minutes, more preferably 10 to 100 minutes. It should be noted that the calcination can be performed once or twice or more. The photo-alignment treatment here is equivalent to the treatment of light irradiation in a state not in contact with the liquid crystal layer.
[0136] The organic solvent used for the above-mentioned cleaning is not particularly limited. Specific examples thereof include water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, 1-methoxy-2-propanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, methyl lactate, diacetone alcohol, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propyl acetate, butyl acetate, or cyclohexyl acetate.
[0137] It should be noted that the liquid crystal alignment film after the brushing treatment can also be further treated as follows so that each area of the liquid crystal alignment film has different liquid crystal orientation capabilities, and the treatment is: by irradiating a portion of the liquid crystal alignment film with ultraviolet rays, the pretilt angle of a portion of the liquid crystal alignment film is changed; on the basis of forming a protective (rasist) film on a portion of the surface of the liquid crystal alignment film, the brushing treatment is performed in a direction different from the previous brushing treatment, and then the protective film is removed. In this case, the visual field characteristics of the obtained liquid crystal display element can be improved. The liquid crystal alignment film preferred in the VA type liquid crystal display element can also be preferably used in the PSA (Polymer sustained alignment) type liquid crystal display element.
[0138] [Step (1-3): Construction of liquid crystal cell]
[0139] (1-3A)
[0140] As described above, two substrates with liquid crystal alignment films are prepared, and liquid crystal is arranged between the two substrates arranged opposite to each other, thereby manufacturing a liquid crystal box. In order to manufacture a liquid crystal box, for example, the following two methods can be listed. The first method is a method known in the past. First, two substrates are arranged opposite to each other with a gap (unit gap) between them in a manner that each liquid crystal alignment film is opposite to each other, and the peripheral parts of the two substrates are bonded together using a sealant. After the liquid crystal is injected into the unit gap divided by the substrate surface and the sealant, the injection hole is sealed to manufacture a liquid crystal box. The second method is a method called ODF (One Drop Fill: liquid crystal dripping) method. A sealant such as a UV-curable sealant is applied at a specified position on one of the two substrates with a liquid crystal alignment film, and after liquid crystal is further dripped into several specified positions on the surface of the liquid crystal alignment film, the substrate of the other side is bonded in a manner that the liquid crystal alignment film is opposite to each other, and the liquid crystal is spread to the entire surface of the substrate, and then the entire surface of the substrate is irradiated with ultraviolet light to cure the sealant, thereby manufacturing a liquid crystal box. In the case of using any of the methods, it is desirable to further heat the liquid crystal used in the liquid crystal cell manufactured as described above to a temperature at which the liquid crystal becomes isotropic and then gradually cool it to room temperature to remove the flow alignment during liquid crystal filling.
[0141] As the sealant, for example, an epoxy resin containing a curing agent and alumina balls as spacers can be used.
[0142] As liquid crystal, there can be listed: nematic liquid crystal and smectic liquid crystal, among which nematic liquid crystal is preferred, for example, Schiff base liquid crystal, azoxy liquid crystal, biphenyl liquid crystal, phenylcyclohexane liquid crystal, ester liquid crystal, terphenyl liquid crystal, biphenylcyclohexane liquid crystal, pyrimidine liquid crystal, dioxane liquid crystal, bicyclooctane liquid crystal, cubane liquid crystal, etc. can be used. In addition, cholesteric liquid crystals such as cholesteryl chloride, cholesteryl nonanoate, cholesteryl carbonate, etc. can also be added to these liquid crystals; chiral agents sold as trade names "C-15" and "CB-15" (Merck Company); strong dielectric liquid crystals such as p-decyloxybenzylidene amino-2-methylbutyl cinnamate, etc. In addition, the liquid crystal can be supplemented with anisotropic dyes. The term "dye" refers to a substance that can concentrate and absorb or deform light in at least a part or the entire range in the visible light region, such as the 400nm or 700nm wavelength range, and the term "anisotropic dye" refers to a substance that can anisotropically absorb light in at least a part or the entire range of the visible light region.
[0143] The color sense of the liquid crystal box can be adjusted by using dyes as described above. The type of anisotropic dye is not particularly limited, for example, black dye or color dye can be used. In the range of not damaging the physical properties, the ratio of anisotropic dye to liquid crystal can be appropriately selected, for example, the anisotropic dye can be included in a ratio of 0.01 to 5 parts by weight relative to 100 parts by weight of the liquid crystal compound, and the ratio can be changed in an appropriate range as needed.
[0144] (1-3B)
[0145] When a PSA type liquid crystal display element is produced, a liquid crystal cell is constructed in the same manner as in (1-3A) above except that a photopolymerizable compound such as the following formula (w-1) to (w-5) is injected or dropped together with the liquid crystal.
[0146]
[0147] Then, the liquid crystal box is irradiated with light while a voltage is applied between the conductive films of a pair of substrates. The voltage applied here can be set to, for example, a direct current or alternating current of 5 to 50 V. In addition, as the irradiated light, for example, ultraviolet rays and visible rays containing wavelengths of 150 to 800 nm can be used, but ultraviolet rays containing wavelengths of 300 to 400 nm are preferred. As the light source of the irradiated light, for example, a low-pressure mercury lamp, a high-pressure mercury lamp, a deuterium lamp, a metal halide lamp, an argon resonance lamp, a xenon lamp, an excimer laser, etc. can be used. It should be noted that the ultraviolet rays in the above-mentioned preferred wavelength range can be obtained by a method of using a light source, for example, with a filter, a diffraction grating, etc. The irradiation amount of light is preferably 100 mJ / cm 2 Above and less than 30000mJ / cm 2 , more preferably 100 to 20000 mJ / cm 2 .
[0148] (1-3C)
[0149] When a coating film is formed on a substrate using a liquid crystal alignment agent containing a compound (polymer or additive) having a photopolymerizable group, a liquid crystal box is constructed in the same manner as in (1-3A) above, and then the following method can also be used: a method for manufacturing a liquid crystal display element by irradiating the liquid crystal box with light while applying a voltage between the conductive films of a pair of substrates. According to this method, the advantages of the PSA mode can be achieved with a small amount of light irradiation. The light irradiation of the liquid crystal box can be performed in a state where the liquid crystal is driven by applying a voltage, or it can be performed in a state where a low voltage is applied to the extent that the liquid crystal is not driven. The applied voltage can be set to, for example, a direct current or alternating current of 0.1 to 30 V. Regarding the conditions of the irradiated light, the description of (1-3B) above can be applied. The light irradiation treatment here is equivalent to the treatment of light irradiation in a state of contact with the liquid crystal layer.
[0150] Furthermore, by attaching a polarizing plate to the outer surface of the liquid crystal cell, the liquid crystal display element of the present invention can be obtained. Examples of the polarizing plate attached to the outer surface of the liquid crystal cell include: a polarizing plate formed by sandwiching a polarizing film called "H film" that stretches and orients polyvinyl alcohol and absorbs iodine with a cellulose acetate protective film; or a polarizing plate composed of the H film itself.
[0151] The liquid crystal display element of the present invention can be effectively used in various devices, for example, it can be used in various display devices such as clocks, portable game consoles, word processors, notebook computers, car navigation systems, portable cameras, PDAs (Personal Digital Assistants), digital cameras, mobile phones, smart phones, various monitors, liquid crystal televisions, information displays, etc.
[0152] As described above, by using the liquid crystal alignment agent of the present invention, it is possible to obtain a liquid crystal alignment film with less afterimages and minimize bright spots even when physical friction such as scratches caused by spacers occurs, and a liquid crystal display element having the liquid crystal alignment film. In addition, the obtained liquid crystal display element has high reliability.
[0153] Example
[0154] The present invention is further described in detail with reference to the following examples, but the present invention is not limited thereto. The abbreviations of the compounds used are as follows.
[0155] (liquid crystal)
[0156] MLC-3019 (manufactured by MERCK, positive liquid crystal).
[0157] (Diamine compound)
[0158] WA-1: A compound represented by the formula [WA-1].
[0159] WA-2: A compound represented by the formula [WA-2].
[0160]
[0161] (Other diamine compounds)
[0162] A1 to A7: compounds represented by formula [A1] to [A7], respectively.
[0163]
[0164] (Boc represents tert-butoxycarbonyl.)
[0165] (Acid dianhydride compound)
[0166] B1 to B3: compounds represented by formula [B1] to [B3], respectively.
[0167]
[0168] (Solvent)
[0169] NMP: N-methyl-2-pyrrolidone.
[0170] BCS: ethylene glycol monobutyl ether.
[0171] GBL: gamma-butyrolactone.
[0172] (additive)
[0173] S-1: 3-glycidoxypropyltriethoxysilane.
[0174] (Crosslinking agent)
[0175] AD-1: a compound represented by the following formula (AD-1).
[0176]
[0177] (Molecular weight determination)
[0178] The molecular weights of the polyimide precursor and the polyimide were measured as follows using a room temperature gel permeation chromatography (GPC) apparatus (GPC-101) (manufactured by Showa Denko K.K.) and columns (KD-803, KD-805) (manufactured by Shodex Corporation).
[0179] Column temperature: 50°C.
[0180] Eluent: N,N-dimethylformamide (as additives, lithium bromide monohydrate (LiBr·H2O) is 30 mmol / L (liter), phosphoric acid / anhydrous crystals (o-phosphoric acid) is 30 mmol / L, and tetrahydrofuran (THF) is 10 mL / L).
[0181] Flow rate: 1.0 mL / min.
[0182] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide (molecular weight: about 900,000, 150,000, 100,000 and 30,000) (manufactured by Tosoh Corporation) and polyethylene glycol (molecular weight: about 12,000, 4,000 and 1,000) (manufactured by Polymer Laboratory).
[0183] (Measurement of Imidization Ratio of Polyimide)
[0184] 20 mg of polyimide powder was added to an NMR (nuclear magnetic resonance) sample tube (NMR standard sampling tube, φ5 (manufactured by Kusano Scientific Co., Ltd.)), deuterated dimethyl sulfoxide (DMSO-d6, 0.05 mass% TMS (tetramethylsilane) mixture) (0.53 mL) was added, and ultrasonic waves were applied to completely dissolve it. The solution was measured for 500 MHz proton NMR using an NMR measuring machine (JNW-ECA500) (manufactured by JEOL DATUM Co., Ltd.). The imidization rate was calculated as follows: the proton derived from the structure that does not change before and after imidization is determined as the reference proton, and the peak integral value of the proton and the proton peak integral value derived from the NH group of the amide acid appearing near 9.5 to 10.0 ppm are used to calculate it using the following formula.
[0185] Imidization rate (%) = (1-α·x / y) × 100
[0186] In the above formula, x is the peak integral value of protons derived from NH groups of amic acid, y is the peak integral value of reference protons, and α is the ratio of the number of reference protons to protons of one NH group of amic acid in the case of polyamic acid (imidation ratio 0%).
[0187] (Viscosity measurement)
[0188] In the synthesis examples or comparative synthesis examples, the viscosity of the polyimide polymer was measured using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) at a sample volume of 1.1 mL, a conical rotor TE-1 (1°34′, R24), and a temperature of 25°C.
[0189] (WA-1) The synthesis was carried out with reference to the following prior art documents.
[0190] Salvatore Zarra, Jack K. Clegg, Jonathan R. Nitschke, Angewandte Chemie International Edition, 52, 18, (4837-4840, Supporting Information: S2-S3), (2013).
[0191] (WA-2) is a new compound that has not been disclosed in literature, and its synthesis method is described in detail below.
[0192] The product described in the following Synthesis Example 1 was obtained by 1 Identification was performed by H-NMR analysis (analysis conditions are as follows).
[0193] Device: BRUKER ADVANCE III - 500MHz.
[0194] Determination solvent: DMSO-d6.
[0195] Reference material: Tetramethylsilane (TMS) (δ0.0ppm for 1 H).
[0196] The abbreviations in the present invention respectively have the following meanings.
[0197] THF: tetrahydrofuran.
[0198] DCE: 1,2-dichloroethane.
[0199] DMAP: N, N-dimethyl-4-aminopyridine.
[0200] <<Monomer Synthesis Example 1 Synthesis of WA-2>>
[0201]
[0202] <Synthesis of compound [1]>
[0203] Into 1,2-dichloroethane (540 g), (4,4'-dinitro-[1,1'-biphenyl]-2,2'-diyl) dimethanol (60.0 g, 0.197 mol), triethylamine (45.9 g, 0.454 mol), N,N-dimethyl-4-aminopyridine (2.39 g, 0.0197 mol) were added, and stirred under ice-cooling. Di-tert-butyl dicarbonate (94.7 g, 0.434 mol) diluted with 1,2-dichloroethane (60 g) was added dropwise while paying attention to heat generation, and after heat generation stopped, stirred at room temperature overnight. After the reaction was completed, stirring was stopped, water (600 g) was added for liquid separation and washing, and liquid separation and extraction were performed using chloroform (300 g × 2 times). The organic phase was concentrated, and the obtained crude product was purified by silica gel column chromatography using a mixed solvent of ethyl acetate / hexane = 2 / 1 (volume ratio), and the obtained solution was concentrated and dried to obtain a crude product of compound [1] (yield: 102 g). The obtained compound was used directly in the next step.
[0204] 1 H-NMR (500MHz) in DMSO-d6: 8.41ppm (s, 2H), 8.33ppm (d, 2H, J=8.5Hz), 7.58ppm (d, 2H, J=8.5Hz), 4.90ppm (s, 4H), 1.39ppm (s, 18H).
[0205] <Synthesis of WA-2>
[0206] The crude product of compound [1] (101 g) and 3% platinum carbon (water-containing product) (8.00 g) were added to tetrahydrofuran (600 g), and stirred overnight at room temperature under a hydrogen atmosphere. After the reaction was completed, the platinum carbon was removed by filtration and the mixture was concentrated under reduced pressure. Methanol was added to the crude product and concentrated again, and dried to obtain WA-2 (yield: 86.6 g, 0.195 mol).
[0207] 1 H-NMR(500MHz)in DMSO-d6: 6.72ppm (d, 2H, J = 8.0Hz), 6.63ppm (d, 2H, J = 2.5Hz), 6.52ppm (d, 1H, J = 2.5Hz) ), 6.50ppm (d, 1H, J=2.0Hz), 5.15ppm (s, 4H), 4.64-4.59ppm (m, 4H), 1.34ppm (s, 18H).
[0208] (Synthesis example 1)
[0209] WA-1 (2.19 g, 9.00 mmol), A1 (1.83 g, 7.50 mmol), A2 (1.72 g, 7.50 mmol), A4 (2.04 g, 6.00 mmol) and B2 (1.12 g, 4.50 mmol) were mixed in NMP (50.6 g), reacted at 50°C for 3 hours, and then B1 (5.32 g, 23.7 mmol) and NMP (30.1 g) were added and reacted at 40°C for 15 hours to obtain a polyamic acid solution [1] (viscosity 384 mPa·s) having a resin solid content concentration of 15% by mass.
[0210] NMP was added to the obtained polyamic acid solution [1] (30.0 g), diluted to 10.0% by mass, and then acetic anhydride (4.83 g) and pyridine (1.50 g) were added as imidization catalysts, and the mixture was reacted at 55° C. for 2.5 hours. The reaction solution was put into methanol (280 mL), and the obtained precipitate was filtered out. The precipitate was washed with methanol and dried under reduced pressure at 100° C. to obtain a polyimide powder (1). The imidization rate of the polyimide was 78.1%, the number average molecular weight was 12322, and the weight average molecular weight was 44438.
[0211] (Synthesis example 2)
[0212] WA-2 (4.00 g, 9.00 mmol), A1 (1.83 g, 7.50 mmol), A2 (1.72 g, 7.50 mmol), A4 (2.04 g, 6.00 mmol) and B2 (1.12 g, 4.50 mmol) were mixed in NMP (50.6 g), reacted at 50°C for 3 hours, and then B1 (5.32 g, 23.7 mmol) and NMP (30.1 g) were added and reacted at 40°C for 15 hours to obtain a polyamic acid solution [2] (viscosity 188 mPa·s) with a resin solid content concentration of 15% by mass.
[0213] NMP was added to the obtained polyamic acid solution [2] (30.0 g), diluted to 10.0% by mass, and then acetic anhydride (4.83 g) and pyridine (1.50 g) were added as imidization catalysts, and the mixture was reacted at 55° C. for 2.5 hours. The reaction solution was put into methanol (280 mL), and the obtained precipitate was filtered out. The precipitate was washed with methanol and dried under reduced pressure at 100° C. to obtain a polyimide powder (2). The imidization rate of the polyimide was 80.1%, the number average molecular weight was 10582, and the weight average molecular weight was 41856.
[0214] (Synthesis example 3)
[0215] A6 (1.19 g, 6.00 mmol), A7 (4.78 g, 24.0 mmol) and B2 (3.75 g, 15.0 mmol) were mixed in NMP (55.1 g), and reacted at 50°C for 3 hours. Then, B3 (4.06 g, 13.8 mmol) and NMP (23.0 g) were added, and the mixture was reacted at 70°C for 15 hours to obtain a polyamic acid solution [3] (viscosity 941 mPa·s) having a resin solid content concentration of 15% by mass.
[0216] The number average molecular weight of the polyamic acid solution [3] was 15244, and the weight average molecular weight was 40724.
[0217] (Comparative Synthesis Example 1)
[0218] A5 (1.91 g, 9.00 mmol), A1 (1.83 g, 7.50 mmol), A2 (1.72 g, 7.50 mmol), A4 (2.04 g, 6.00 mmol) and B2 (1.12 g, 4.50 mmol) were mixed in NMP (50.6 g), reacted at 50°C for 3 hours, and then B1 (5.32 g, 23.7 mmol) and NMP (30.1 g) were added and reacted at 40°C for 15 hours to obtain a polyamic acid solution [R1] (viscosity 365 mPa·s) with a resin solid content concentration of 15% by mass.
[0219] NMP was added to the obtained polyamic acid solution [R1] (30.0 g), diluted to 10.0 mass%, and then acetic anhydride (4.83 g) and pyridine (1.50 g) were added as imidization catalysts, and the mixture was reacted at 55 ° C for 2.5 hours. The reaction solution was put into methanol (280 mL), and the obtained precipitate was filtered out. The precipitate was washed with methanol and dried under reduced pressure at 100 ° C to obtain a polyimide powder (R1). The imidization rate of the polyimide was 76.1%, the number average molecular weight was 10958, and the weight average molecular weight was 39958.
[0220] <Preparation of Liquid Crystal Alignment Agent>
[0221] In Examples and Comparative Examples, preparation examples of liquid crystal aligning agents are described. Using the liquid crystal aligning agents obtained in Examples and Comparative Examples, liquid crystal display elements were produced and various evaluations were performed.
[0222] (Example 1)
[0223] NMP (22.0 g) was added to the polyimide powder (1) (3.00 g) obtained in Synthesis Example 1, and the mixture was stirred at 80° C. for 15 hours to dissolve the mixture. The polyamic acid solution [3] (3.30 g) obtained in Synthesis Example 3, NMP (1.35 g), GBL (3.675 g), BCS (3.00 g), a 10% by mass dilution solution of AD-1 in NMP (0.248 g), and a 1% by mass dilution solution of S-1 in GBL (0.825 g) were added to the solution (2.75 g), and the mixture was stirred at room temperature for 5 hours to obtain a liquid crystal aligning agent (V-1). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and the solution was confirmed to be a uniform solution.
[0224] (Example 2)
[0225] A liquid crystal aligning agent (V-2) was obtained in the same manner as in Example 1, except that the polyimide powder (2) was used instead of the polyimide powder (1) in Example 1. Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.
[0226] (Comparative Example 1)
[0227] A liquid crystal aligning agent (W-1) was obtained in the same manner as in Example 1, except that the polyimide powder (R1) was used instead of the polyimide powder (1) in Example 1. Abnormalities such as turbidity and precipitation were not observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.
[0228] <Preparation of samples for seal adhesion evaluation>
[0229] The adhesion evaluation sample was prepared as follows. The liquid crystal alignment agent (V-1) and (V-2) obtained in the example and the liquid crystal alignment agent (W-1) obtained in the comparative example were applied to a 30 mm × 40 mm ITO substrate by spin coating. After drying on a hot plate at 80°C for 120 seconds, it was calcined in a hot air circulation oven at 230°C for 20 minutes to form a coating film with a film thickness of 100 nm, and a substrate with a liquid crystal alignment film was obtained.
[0230] Prepare two substrates obtained in this way, apply a bead-shaped spacer with a diameter of 4 μm on the liquid crystal orientation film surface of one substrate, and then drip a sealant (XN-1500T manufactured by Kyoritsu Chemical Industry Co., Ltd.). Next, set the liquid crystal orientation film surface of the other substrate to the inner side, and bond them in such a way that the overlapping width around the substrates is 1 cm each. At this time, adjust the amount of sealant dripped in such a way that the diameter of the sealant after bonding is 3 mm. After fixing the two bonded substrates with a clamp, irradiate 3J of 365nm light, thermally cure it at 120°C for 1 hour, and prepare a sample for evaluating adhesion.
[0231] <Evaluation of Adhesion>
[0232] Then, the sample substrate obtained above was subjected to a table-top precision universal testing machine AGS-X500N manufactured by Shimadzu Corporation. After fixing the ends of the upper and lower substrates, the substrate was pressed from the upper part of the center part to measure the force (N) during peeling. The case where (N) was less than 3.50 was defined as "poor", and the case where (N) was 3.50 or more was defined as "good". The results are shown in Table 1.
[0233] <Evaluation of film strength (film hardness)>
[0234] The liquid crystal aligning agent was applied to the ITO surface of the glass substrate with an ITO electrode on the entire surface by spin coating. After drying on a hot plate at 80°C for 2 minutes, a coating film with a thickness of 100 nm was formed. The coating film surface was sprayed with 150 mJ / cm 2 The substrate was irradiated with polarized ultraviolet rays in a manner to implement an orientation treatment. Then, an IR type oven was used to bake at 230°C for 30 minutes to obtain a substrate with a liquid crystal orientation film. The liquid crystal orientation film was rubbed with a rayon cloth (roller diameter: 120 mm, roller rotation speed: 1000 rpm, moving speed: 20 mm / sec, pressing length: 0.6 mm). The substrate was measured using a HZ-V3 haze meter manufactured by SUGA Testing Machine Co., Ltd. The haze value of 0.3 or more was defined as "poor", and the haze value of less than 0.3 was defined as "good", and an evaluation was performed. The results are shown in Table 1.
[0235] <Preparation of a liquid crystal cell for evaluating liquid crystal orientation>
[0236] Hereinafter, a method for producing a liquid crystal cell for evaluating the liquid crystal orientation will be described.
[0237] A liquid crystal box having a liquid crystal display element of the FFS method was produced. First, a substrate with electrodes was prepared. The substrate was a glass substrate with a size of 30 mm × 35 mm and a thickness of 0.7 mm. On the substrate, as the first layer, an IZO electrode constituting a counter electrode was formed on the entire surface. On the counter electrode of the first layer, as the second layer, a SiN (silicon nitride) film formed by a CVD method was formed. The film thickness of the second layer of the SiN film is 500 nm, and it functions as an interlayer insulating film. On the second layer of the SiN film, as the third layer, a comb-shaped pixel electrode formed by patterning the IZO film was arranged, forming two types of pixels, the first pixel and the second pixel. The size of each pixel is 10 mm long and about 5 mm wide. At this time, the counter electrode of the first layer and the pixel electrode of the third layer are electrically insulated due to the action of the SiN film of the second layer.
[0238] The pixel electrode of the third layer has a comb-like shape formed by arranging a plurality of electrode elements in the shape of a < symbol with a bent central portion, similar to the drawings described in Japanese Patent Laid-Open No. 2014-77845 (Japanese Patent Gazette). The width of each electrode element in the short dimension direction is 3 μm, and the interval between the electrode elements is 6 μm. The pixel electrode forming each pixel is configured by arranging a plurality of electrode elements in the shape of a < symbol with a bent central portion, so the shape of each pixel is not a rectangular shape, but a shape similar to the bold < symbol with a bent central portion like the electrode elements. Furthermore, each pixel is divided into upper and lower parts with the bent portion in the center as the boundary, and has a first area on the upper side of the bent portion and a second area on the lower side.
[0239] Comparing the first area and the second area of each pixel, the formation direction of the electrode elements constituting the pixel electrodes is different. That is, in the first area of the pixel, the electrode elements of the pixel electrode are formed in a manner to form an angle of +80° (clockwise), and in the second area of the pixel, the electrode elements of the pixel electrode are formed in a manner to form an angle of -80° (clockwise). That is, in the first area and the second area of each pixel, the directions of the rotation action (in-plane / switching) of the liquid crystal in the substrate surface induced by the voltage application between the pixel electrode and the opposing electrode are formed in opposite directions.
[0240] Next, after filtering the liquid crystal alignment agent obtained in the synthesis example and the comparative synthesis example with a 1.0 μm filter, apply it to the prepared substrate with electrodes by spin coating. Then, dry it on a heating plate set at 80°C for 120 seconds. Next, use the exposure device manufactured by USHIO Electric Co., Ltd.: APL-L050121S1S-APW01 to irradiate the substrate with linearly polarized ultraviolet rays from a vertical direction through a wavelength selection filter and a polarizing plate. At this time, the direction of the polarization plane is set as follows: the direction of the polarization plane of the polarized ultraviolet rays projected onto the line segment of the substrate becomes a direction inclined 80° relative to the third layer of IZO comb-tooth electrodes. Next, it was calcined at 230°C for 30 minutes in an IR (infrared) type oven to obtain a substrate with a polyimide liquid crystal alignment film with a film thickness of 100 nm that had been subjected to orientation treatment. In addition, as an opposing substrate, a substrate with a polyimide liquid crystal orientation film was obtained, and the substrate with a polyimide liquid crystal orientation film was obtained by applying an orientation treatment to a glass substrate with a columnar spacer having an ITO electrode formed on the back and a height of 4μm in the same manner as described above. The two substrates with liquid crystal orientation films were set as a group, and a sealant was printed in the form of a liquid crystal injection port left on one substrate, and the other substrate was bonded and crimped in a manner such that the liquid crystal orientation film faces were facing each other and the polarization plane of the polarized ultraviolet rays was projected onto the line segment of the substrate in parallel. Then, the sealant was cured to produce an empty box with a box gap of 4μm. Liquid crystal MLC-3019 (positive liquid crystal made by MERCK) was injected into the empty box by a reduced pressure injection method, and the injection port was sealed to obtain an FFS liquid crystal box. Then, the obtained liquid crystal box was heated at 120°C for 30 minutes, and after being left overnight at 23°C, it was used to evaluate the liquid crystal orientation.
[0241] <Evaluation of Liquid Crystal Orientation>
[0242] Using this liquid crystal cell, the case where flow orientation was confirmed was defined as "poor", and the case where flow orientation was not confirmed was defined as "good".
[0243] [Table 1]
[0244]
[0245] From the above results, it can be seen that in the adhesion evaluation, the liquid crystal alignment films obtained using the liquid crystal alignment agents of the diamine compounds WA-1 and WA-2 show higher adhesion than the liquid crystal alignment film obtained using the liquid crystal alignment agent of the diamine compound A5. Specifically, this is reflected in the comparison between Examples 1 to 2 and Comparative Example 1 shown in Table 1.
[0246] Furthermore, in the film strength evaluation, it was found that the liquid crystal alignment films obtained using the liquid crystal alignment agents of diamine compounds WA-1 and WA-2 showed higher film strength than the liquid crystal alignment film obtained using the liquid crystal alignment agent of diamine compound A5. Specifically, this was shown in the comparison between Examples 1 to 2 and Comparative Example 1 shown in Table 1.
[0247] And it turns out that the liquid crystal aligning film obtained from the liquid crystal aligning agent using the diamine compound WA-1 and WA-2 expresses the liquid crystal orientation equivalent to the liquid crystal aligning film obtained from the liquid crystal aligning agent using the diamine compound A5.
[0248] From the above, when WA-1 or WA-2 having a biphenyl skeleton and having a specific side chain is used, the seal adhesion and the film strength can be improved while the liquid crystal orientation is maintained.
[0249] Industrial Applicability
[0250] Liquid crystal display elements using a liquid crystal alignment film obtained from the liquid crystal alignment agent of the present invention can be preferably used in liquid crystal display elements. In addition, these elements are useful in liquid crystal displays for display purposes, and are also useful in dimming windows and optical shutters for controlling the transmission and blocking of light.
Claims
1. A liquid crystal aligning agent comprising at least one polymer selected from a polyimide precursor including a structural unit represented by the following formula (6) and a polyimide which is an imide product of the polyimide precursor, In formula (6), X1 is a tetravalent organic group derived from a tetracarboxylic acid derivative, Y1 is a divalent organic group derived from a diamine having a structure of formula (1), R4 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, In formula (1), A represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, a benzyl group, a p-methoxybenzyl group, an acetyl group, a benzoyl group, a tert-butoxycarbonyl group, a 9-fluorenylmethoxycarbonyl group or a R1R2R3Si group, and R1, R2 and R3 each independently represent an alkyl group having 1 to 3 carbon atoms or a phenyl group.
2. The liquid crystal alignment agent according to claim 1, wherein In the formula (6), the structure of X1 is at least one selected from the following structures, 3. The liquid crystal aligning agent according to any one of claims 1 to 2, wherein The structural unit represented by formula (6) accounts for 10 mol% or more of all the structural units of the polymer. 4 . A liquid crystal aligning film obtained using the liquid crystal aligning agent according to claim 1 . A liquid crystal display element comprising the liquid crystal alignment film according to claim 4 .
6. A polymer, which is at least one polymer selected from a polyimide precursor containing a structural unit represented by the following formula (6) and a polyimide which is an imide product of the polyimide precursor, In formula (6), X1 is a tetravalent organic group derived from a tetracarboxylic acid derivative, Y1 is a divalent organic group derived from a diamine having a structure of formula (1), R4 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, In formula (1), A represents an alkyl group having 1 to 3 carbon atoms, benzyl, p-methoxybenzyl, acetyl, benzoyl, tert-butoxycarbonyl, 9-fluorenylmethoxycarbonyl or R1R2R3Si group, and R1, R2 and R3 each independently represent an alkyl group having 1 to 3 carbon atoms or a phenyl group.
Citation Information
Patent Citations
Liquid crystal aligning agent
JP1998338880A
Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element
JP2007286597A
Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element, and polyamic acid and polyimide used for manufacturing these
JP2012173514A
In-plane switching type liquid crystal display element
JP2014077845A
Liquid crystal alignment agent, liquid crystal alignment film and liquid crystal display
JP2014224978A